2019
DOI: 10.1016/j.jspr.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Paddy rice stored under hermetic conditions: The effect of relative humidity, temperature and storage time in suppressing Sitophilus zeamais and impact on rice quality

Abstract: The aim of this study was to analyse the effect of relative humidity in suppressing Sitophilus zeamais, in paddy rice stored under hermetic conditions, during four and seven months, at different average temperatures, as well as the impact on rice quality. Hermetic bags, GrainPro ® SuperGrainbag ® Farm™, were used to store two rice varieties under three different relative humidities: 67%, 75% and 85% RH, and average temperatures of 14 C, 17 C and 24 C, both monitored by Hobo ® Data loggers, with the probe place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The reproduction potentials of stubborn insects can be blocked by modifying the storage atmosphere. Carvalho et al (2019) observed changes in the response of stored-product insects under different O2 and CO2 concentrations. The findings of Diarra and Amoah (2019) revealed that hermetic bagging could increase storage temperature to 27 °C and lower O2, R.H. and moisture to 6.4 %, <70 % and <14 %, respectively in tropical areas, creating an atmosphere unfavorable to insect activities and mold growth.…”
Section: Causes Of Postharvest Lossesmentioning
confidence: 88%
See 1 more Smart Citation
“…The reproduction potentials of stubborn insects can be blocked by modifying the storage atmosphere. Carvalho et al (2019) observed changes in the response of stored-product insects under different O2 and CO2 concentrations. The findings of Diarra and Amoah (2019) revealed that hermetic bagging could increase storage temperature to 27 °C and lower O2, R.H. and moisture to 6.4 %, <70 % and <14 %, respectively in tropical areas, creating an atmosphere unfavorable to insect activities and mold growth.…”
Section: Causes Of Postharvest Lossesmentioning
confidence: 88%
“…The gas composition of the storage atmosphere affects insect activities in general. Insect activities significantly decrease under a CO2 saturated atmosphere and higher temperature (Carvalho et al, 2019). A modified atmosphere with higher CO2 and low O2 concentrations provides a safe condition for grain storage (Dowell and Dowell, 2017).…”
Section: Causes Of Postharvest Lossesmentioning
confidence: 99%
“…Variety JH6 had the smallest decreases in appearance, flavour, and comprehensive score, with the score for appearance decreasing by 0.8, the score for flavour decreasing by 0.7, and the comprehensive score decreasing by 7.5. Excessive storage times and high storage temperatures will lead to grain cracking [97,98]. Our research team also compared the microstructure of fresh rice with those of rice that had been stored for one year.…”
Section: T 5 Storage Periodmentioning
confidence: 99%
“…The rice that was stored for one year had obvious micro-cracks. Excessive storage times and high storage temperatures will lead to grain cracking [97,98]. Our research team also compared the microstructure of fresh rice with those of rice that had been stored for one year.…”
Section: T 5 Storage Periodmentioning
confidence: 99%
“…The content of amylose soluble in hot water in rice decreases with increasing storage time, while the content of amylose insoluble in hot water gradually increases. Studies have pointed out that in rice stored for one year (20–25 °C), the amylose content increases by 4.94%, the insoluble amylose content increases by 4.26%, and the branched fixed flour content decreases by 6.05% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%